2021
DOI: 10.1002/adfm.202103706
|View full text |Cite
|
Sign up to set email alerts
|

Plasmomechanical Systems: Principles and Applications

Abstract: Extreme confinement of electromagnetic waves and mechanical displacement fields to nanometer dimensions through plasmonic nanostructures offers unprecedented opportunities for greatly enhanced interaction strength, increased bandwidth, lower power consumption, chip-scale fabrication, and efficient actuation of mechanical systems at the nanoscale. Conversely, coupling mechanical oscillators to plasmonic nanostructures introduces mechanical degrees of freedom to otherwise static plasmonic structures thus giving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 107 publications
0
14
0
Order By: Relevance
“…3,4 More recently, it has been shown that there is a strong interaction between the plasmonic and vibrational (mechanical) properties of nano-objects that can be used to develop nanooptomechanics based on metal nanoparticles. [5][6][7] However, while the control of the plasmonic properties tends to be a mature technology, the control of the vibrational properties of nanoobjects and their assembly and their interaction with light are in their infancy. Following the example of developments in the field of plasmonics, the tools for measuring the acoustic vibrations of nano-objects are evolving and allow to constantly improve our understanding of the mechanisms involved in light-vibration interactions in nano-objects (not necessarily metallic) and thus to envisage the joint engineering of the acoustic and optical properties of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 More recently, it has been shown that there is a strong interaction between the plasmonic and vibrational (mechanical) properties of nano-objects that can be used to develop nanooptomechanics based on metal nanoparticles. [5][6][7] However, while the control of the plasmonic properties tends to be a mature technology, the control of the vibrational properties of nanoobjects and their assembly and their interaction with light are in their infancy. Following the example of developments in the field of plasmonics, the tools for measuring the acoustic vibrations of nano-objects are evolving and allow to constantly improve our understanding of the mechanisms involved in light-vibration interactions in nano-objects (not necessarily metallic) and thus to envisage the joint engineering of the acoustic and optical properties of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…The small dimensions of nano-objects are at the origin of the appearance of original optical properties resulting from the confinement of excitons in semiconductor nanoparticles and the localized surface plasmons in metallic ones. , The latter are now widely used in many applications thanks to the recent development of fabrication and characterization techniques, paving the way for nanoplasmonic engineering linking both the intrinsic plasmonic properties of individual particles and their interactions with their environment or each other. , More recently, it has been shown that there is a strong interaction between the plasmonic and vibrational (mechanical) properties of nano-objects that can be used to develop nano-optomechanics based on metal nanoparticles. However, while the control of the plasmonic properties tends to be a mature technology, the control of the vibrational properties of nano-objects and their assembly and interaction with light are in their infancy. Following the example of developments in the field of plasmonics, the tools for measuring the acoustic vibrations of nano-objects are evolving and allow us to constantly improve our understanding of the mechanisms involved in light–vibration interactions in nano-objects (not necessarily metallic) and thus to envisage the joint engineering of the acoustic and optical properties of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the resonant excitation of these plasmonic nanostructures leads to a strong absorption of the incident light, generating photo-induced thermal effect that can be exploited for actuation of mechanical systems at the nanoscale. Therefore, these systems offer optical and mechanical degrees of freedom for different kinds of applications including active control of nano-mechanical motion transduction and amplification of weak external stimuli [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…In most of these applications, metasurfaces comprise specific spatial distributions of nanoantennas or arrays with a fixed periodicity or aperiodic patterns. The typical geometry includes a monolayer of nanoparticles exhibiting plasmonic properties supported by a rigid or flexible substrate [15,16]. In this vast scenario of possibilities, a relevant role is played by phased arrays showing collective resonances or so-called lattice plasmon modes (LPMs).…”
Section: Introductionmentioning
confidence: 99%